Assessing the impact of medication therapy management on health outcomes in underserved populations - Bharti Sao, Rupali; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
The medication therapy management service in collaboration with psychiatrist was initiated in order to enhance pharmacotherapy and the patient care process. The proactive role of the pharmacist in initiating and providing Patient medication review, Pharmaceutical care plan, Evidence based drug Information and intervention services under MTM services resulted in optimal clinical and economic outcomes for patients with depression, BPAD, ADS, and schizophrenia. Significant improvement in the clinical condition, medication adherence, quality of life and patient satisfaction was observed in test group patients compared to the control group. The pharmacist - psychiatrist collaborative approach helped in early detection and resolution of DRPs, provision of patient education and clinical care services that further resulted in improved clinical and humanistic outcomes besides reduction in economic burden. Patients with psychiatric illness are often has associated with drug related problems. Due to the rapid rise in psychotropic drugs and the increasing prevalence of concurrent medical conditions, pharmaceutical regimens are more complex and more likely to cause drug interactions, side effects, poor adherence, and higher costs. Pharmacists in multidisciplinary psychiatry team as educators, consultants, researchers, and Medication Therapy Management (MTM) services providers for nearly 40 years. To assess the impact of pharmacist-psychiatrist initiated medication therapy management services. The pharmacist - psychiatrist collaborative approach helped in early detection and resolution of DRPs, provision of patient education and clinical care services that further resulted in improved clinical and humanistic outcomes besides reduction in economic burden.